Wiley IFRS practical implementation guide and workbook - Mirza, Abbas Ali.; Holt, Graham J. (Hoboken, New Jersey : John Wiley & Son, Inc., 2011)
The large-scale, global adoption of the International Financial Reporting Standards (IFRS) has created an urgent need for a one-step resource with lucid explanations and comprehensive guidance of these complex standards. This reference guide includes easy-to-understand explanations of IFRS/IAS standards, case studies with solutions, and illustrations with multiple choice questions and solutions. The book facilitates understanding of the practical implementation issues involved in applying these complex "principles-based" standards.
1. Introduction to International Financial Reporting Standards -- 2. IASB Framework -- 3. Presentation of Financial Statements (IAS 1) -- 4. Inventories (IAS 2) -- 5. Statement of Cash Flows (IAS 7) -- 6. Accounting Policies, Changes in Accounting Estimates59and Errors (IAS 7) -- 7. Events After the Reporting Period (IAS 10) -- 8. Construction Contracts (IAS 11) -- 9. Income Taxes (IAS 12) -- 10. Property, Plant, and Equipment (IAS 16) -- 11. Leases (IAS 17) -- 12. Revenue (IAS 18) -- 13. Employee Benefits (IAS 19) -- 14. Accounting for Government Grants and Disclosure of Government Assistance (IAS 20) -- 15. The Effects of Changes in Foreign Exchange Rates (IAS 21) -- 16. Borrowing Costs (IAS 23) -- 17. Related-Party Disclosures (IAS 24) -- 18. Accounting and Reporting by Retirement Benefit Plans (IAS 26) -- 19. Consolidated and Separate Financial Statements (IAS 27) -- 20. Investments in Associates (IAS 28) -- 21. Financial Reporting in Hyperinflationary Economies (IAS 29) -- 22. Interests in Joint Ventures (IAS 31) -- 23. Financial Instruments: Presentation (IAS 32) -- 24. Financial Instruments: Recognition and Measurement (IAS 39) -- 25. Earnings Per Share (IAS 33) -- 26. Interim Financial Reporting (IAS 34) -- 27. Impairment of Assets (IAS 36) -- 28. Provisions, Contingent Liabilities, and Contingent Assets (IAS 37) -- 29. Intangible Assets (IAS 38) -- 30. Investment Property (IAS 40) -- 31. Agriculture (IAS 41) -- 32. First-Time Adoption of International Financial Reporting Standards (IFRS 1) -- 33. Share-Based Payments (IFRS 2) -- 34. Business Combinations (IFRS 3) -- 35. Insurance Contracts (IFRS 4) -- 36. Noncurrent Assets Held for Sale and Discontinued Operations (IFRS 5) -- 37. Exploration for and Evaluation of Mineral Resources(IFRS 6) -- 38. Financial Instruments: Disclosures (IFRS 7) -- 39. Operating Segments (IFRS 8) -- 40. Financial Instruments (IFRS 9) -- 41. IFRS for SMEs.
Includes index.
Keywords: ACCOUNTING STANDARDS